2018
DOI: 10.3390/nu10111676
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Feeding Practices for South Asian Young Children Living in High-Income Countries: A Systematic Review

Abstract: Sub-optimal nutrition among South Asian (SA) children living in high-income countries is a significant problem. High rates of obesity have been observed in this population, and differential complementary feeding practices (CFP) have been highlighted as a key influence. Our aim was to undertake a systematic review of studies assessing CFP in children under two years of age from SA communities living in high-income countries, including dietary diversity, timing, frequency and promotors/barriers. Searches covered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 38 publications
0
27
0
1
Order By: Relevance
“…The theoretical framework of this study was underpinned by the socio-ecological model, which considers that any health behavior has many levels of influence and interplay between several factors, with a focus on the social and/or community environment [ 23 , 24 ]. This study is an extension of the Nurture Early for Optimal Nutrition (NEON) project, which aims to support optimal IYCF in ethnic minority families living in the UK, since feeding practices, food practices, and behaviors during early experiences can carry over into later childhood and adulthood, in an effort to prevent the development of cardiovascular diseases and co-morbidities [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical framework of this study was underpinned by the socio-ecological model, which considers that any health behavior has many levels of influence and interplay between several factors, with a focus on the social and/or community environment [ 23 , 24 ]. This study is an extension of the Nurture Early for Optimal Nutrition (NEON) project, which aims to support optimal IYCF in ethnic minority families living in the UK, since feeding practices, food practices, and behaviors during early experiences can carry over into later childhood and adulthood, in an effort to prevent the development of cardiovascular diseases and co-morbidities [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…topic guides Topic guides followed a consistent structure but were tailored to the participant to encourage a progressive depth of information discussed. The literature [28][29][30][31][32] informed community and key informant and health professional interview tool guides. 'Family' topic guides were modified based on findings from these prior phases and tailored to family members (e.g.…”
Section: Focus Group Discussionmentioning
confidence: 99%
“…NEON 1 follows a sequential design for evidence generation, beginning with a systematic review series of the literature on infant feeding and care practices in Bangladeshi and other SA families living in: India, Pakistan, Bangladesh and high-income setting. [28][29][30][31][32] This paper presents the results of the subsequent qualitative formative study phase, with participants from 'community', 'key informant', 'health professional' and 'family' groups (across generations), as informed by the multiple levels of the socioecological framework. 33 Evidence from the literature and qualitative study informed an adapted PLA group approach 34 to optimise infant feeding and care practices among Bangladeshi infants aged 6-23 months and will be described elsewhere.…”
Section: Methodology Study Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Imdad, Yakoob & Bhutta reported that educated mothers place high emphasis on feeding nutrient‐rich animal source foods as a diet diversification. Obviously, this might vary again according to ethnicity, residence region and cultural aspects .…”
Section: Discussionmentioning
confidence: 99%